Leiomyoma in the Douglas' pouch - Jandrić-Kočić, Marijana C; Knežević, Snežana (Medicinski časopis, 2025)
Leiomyomas (myoma, fibromyoma or fibroid) are benign tumors of smooth muscle cells. They are predominantly localized in the body of the uterus, but they can also develop in the broad ligament, ovaries, cervix, Douglas space and round ligament. Their frequency ranges from 5.4 to 77%, depending on the population examined or the applied diagnostic technique. Most leiomyomas are asymptomatic, but can present with a wide range of symptoms. Treatment  includes pharmacological treatment and surgical treatment.A patient with a leiomyoma of the Douglas space coexisted with leiomyomas of the uterine body. Apart from intense pain in the lower part of the stomach, she had no other symptoms. Abdominal ultrasound examination, transvaginal ultrasound examination and computer tomography revealed an enlarged, myomatous uterus and a tumoral change on the right ovary. In an extensive operation, the uterus and both fallopian tubes were removed. The final diagnosis of a tumor changes in Douglas' space, which was initially considered a potentially malignant tumor of the right ovary, was established by a pathohistological examination after the operation.Leiomyomas are relatively common benign tumors of the uterine body. Their early diagnosis during a gynecological examination enables timely treatment that avoids hysterectomy and maintains fertility. Leiomyomas of atypical localization have a low incidence and an unclear clinical picture, and their final diagnosis is predominantly made after surgery.
Keywords: tumor, smooth muscle cells, reproductive system